Trichoderma asperellum Inoculation as a Tool for Attenuating Drought Stress in Sugarcane - Scudeletti, Daniele; Crusciol, Carlos Alexandre Costa; Bossolani, João William; Moretti, Luiz Gustavo; Momesso, Letusa; Servaz Tubaña, Brenda; de Castro, Sérgio Gustavo Quassi; De Oliveira, Elisa Fidêncio; Hungria, Mariangela (Frontiers in Plant Science, 2021)
Drought stress is an important concern worldwide that reduces crop yield and quality. To alleviate this problem, Trichoderma asperellum has been used as a plant growth promote fungi capable of inducing plant tolerance to biotic and abiotic stresses. Here, we examined the effect of T. asperellum inoculation on sugarcane plants above and belowground development under drought stress, and investigated the role of this fungus on inducing tolerance to drought at physiological and biochemical levels. The experiment was performed in pots under greenhouse conditions, with four treatments and four replicates. The treatments consisted of sugarcane plants inoculated or not with T. asperellum and grown under drought stress and adequate water availability. Drought-stressed sugarcane plants inoculated with T. asperellum changed the crop nutrition, and chlorophylls and carotenoids concentration, resulting in increased photosynthesis rate, stomatal conductance and water use efficiency compared to the non-inoculated plants. In addition, the antioxidant metabolism also changed, increasing the SOD and POD enzyme activities, as well as the proline concentration and sugar portioning. This cascade effects enhanced the root and stalk development, demonstrating that the T. asperellum inoculation is an important tool to alleviate the negative effects of drought stress in sugarcane. Future studies should be performed to elucidate if T. asperellum should be reapplied to the sugarcane ratoons.